2020
DOI: 10.22271/chemi.2020.v8.i5q.10468
|View full text |Cite
|
Sign up to set email alerts
|

Hydroponic vegetable cultivation

Abstract: Many challenges have come to the limelight in recent years due to a rapid increase in the world population. One of these challenges is the reduction of the per capita land available for soil-based agriculture, leading to other agricultural and environmental problems. Under these critical circumstances, it became necessary to develop advanced technologies and techniques to withstand the current situation. While several studies have been carried out on soil and in vitro plant cultivation, few of these are based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
0
0
Order By: Relevance
“…The regular monitoring and adjustment of pH level and nutrient solution composition are necessary to provide plants with adequate nutrition. Improper balancing can lead to nutrient deficiencies or excesses, which in turn can negatively affect plant growth [19].…”
Section: Current Studymentioning
confidence: 99%
“…The regular monitoring and adjustment of pH level and nutrient solution composition are necessary to provide plants with adequate nutrition. Improper balancing can lead to nutrient deficiencies or excesses, which in turn can negatively affect plant growth [19].…”
Section: Current Studymentioning
confidence: 99%
“…Previous research has shown that hydroponic crops grow 30-50% faster than conventional ones [32]. As an example, the open agriculture yield for a tomato crop is on average 5-12 tons per acre, while for hydroponic cultivation yield, it can reach 180-200 tons per acre [33,34]. Additionally, this type of cultivation is not labor-intensive, as production is more automated and industrialized thanks to the use of specialized equipment [35].…”
Section: Swot Analysismentioning
confidence: 99%